The Emergence and Prevalence of Persian Literature in Albania - عبدالله رجبی; حسینعلی قبادی; غلامحسین غلامحسین زاده; ناصر نیکوبخت (تاریخ ادبیات)
Despite the distance between Iran and Albania, Iranian culture and civilization have had a significant impact on Albanian culture. Historians are surprised by the extent influence of Persian literature and Iranian civilization in general, in the Ottoman territory, particularly in the Balkans. Research shows that Iranian culture as software with the support of Islam has entered Albania along with the hardware of the Ottoman army and during five centuries of Ottoman rule over this country, as a language of literature and Sufism and culture has progressed with acceptance. Out of love and interest, Albanians have introduced and promoted this language and literature. Some of them even wrote poems in this language or created scientific, literary and cultural works in Albanian language based on the classical Persian writing pattern. In this article, we aim to explain how and why Persian literature is expanding in Albania and to analyze the performance of Albanian scholars in the field of Persian literature.